Right of access to origins in the context of adoption: A psychological perspective on judicial mediation - Pinho, Patricia Glycerio Rodrigues (2022)
Since 2009, the adoptees’ right to access their origins is assured by law in Brasil.   However,unlike other countries, there have not yet been debates about the scope of this right, which includes the possibility of knowledge and contact with the biological family. In reports of adoptees , the search has been configured as a central and current issue, demanding, therefore, the realization of more studies and reflections on the subject. Due to the relevance of the problem, this article investigates the amplitude of the right to access origins in the context of adoption, focusing on the claims for mediation addressed  to the Justice in procedures referring to the search for origins, in national adoptions. In order to achieve this objective, we present an illustration of a case that took place at one of the Juveniles Courts of the State of Rio de Janeiro, in which the mother sought the Judiciary in order to establish contact with her daughter, who had been voluntarily relinquished 30 years ago. The discussion was based on later interviews carried out with those involved, focusing on the intervention of Justice in the case. We realized that the lack of  specific protocols for situations  like this, almost  prevented the technical intervention that provided contact between families. Finally, we argue the importance of systematizing the procedures to receive  demands of access to origins, whether initiated by the adoptee or by the biological family.